1982
DOI: 10.1136/bmj.284.6332.1835-a
|View full text |Cite
|
Sign up to set email alerts
|

Prednisone in amiodarone-induced thyrotoxicosis.

Abstract: under intensive care observation may be a safe alternative to mechanical ventilation in patients with severe pneumatosis cystoides and chronic respiratory insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 3 publications
0
12
0
2
Order By: Relevance
“…It is not unusual for AIT to require multiple drugs (consecutively or in combination) treatment before metabolic control is attained (2, 3). Nevertheless, some evidence suggests that type II AIT can more easily be treated by glucocorticoid regimen alone (4,5). With the exception of the isolated small thyroid nodule, our patient fulfilled the diagnostic criteria of type II AIT: reduced or absent 123 I-uptake, no hypoechogenic pattern by ultrasound, negative thyroid antibodies.…”
mentioning
confidence: 80%
“…It is not unusual for AIT to require multiple drugs (consecutively or in combination) treatment before metabolic control is attained (2, 3). Nevertheless, some evidence suggests that type II AIT can more easily be treated by glucocorticoid regimen alone (4,5). With the exception of the isolated small thyroid nodule, our patient fulfilled the diagnostic criteria of type II AIT: reduced or absent 123 I-uptake, no hypoechogenic pattern by ultrasound, negative thyroid antibodies.…”
mentioning
confidence: 80%
“…Although some authors have reported successful control of IIT, including AIIT, by thyroidectomy, it should be taken into account that surgery carries high risk in cardiac patients with un controlled thyrotoxicosis. Recently, Wimpfheimer et al [71 ], Léger et al [ 15] and Simon et al [72] reported in small series that the administration of systemic corticosteroids in association with thionamides produced fa vorable effects. These results, however, need to be confirmed in larger series of AIIT patients.…”
Section: Therapy O F Aiitmentioning
confidence: 99%
“…In contrast to AIT, AIH is more frequent in females with a female to male ratio of 1.5:1 [86]. AIH patients are also older than AIT with circulating thyroid autoantibodies seen in almost 53% of AIH patients with underlying thyroid abnormalities especially Hashimoto's thyroiditis [87].…”
Section: Tips and Tricksmentioning
confidence: 99%